1993
DOI: 10.1182/blood.v82.3.931.931
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the high-affinity receptor for IgG (Fc gamma RI; CD64) in enhanced tumor cell cytotoxicity of neutrophils during granulocyte colony-stimulating factor therapy

Abstract: Three different classes of Fc receptors for IgG (Fc gamma R) are currently distinguished in humans, of which polymorphonuclear phagocytes (PMN) normally express both low-affinity receptor classes-- Fc gamma RII (CD32) and Fc gamma RIII (CD16). During therapy with granulocyte colony-stimulating factor (G-CSF), neutrophils from patients with various malignancies and different hematologic disorders were found to additionally express high levels of the receptor with high affinity for IgG (Fc gamma RI; CD64). For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…Importantly, PMN from patients who have been treated with recombinant human G‐CSF also express FcγRI, the high affinity receptor for IgG 119. Consequently, these PMN are more effective in inducing ADCC than are PMN from healthy, untreated donors 120. The receptor for IgA (FcαRI) is also constitutively expressed by PMN and in these cells seems to be the most potent of the Fc receptors for the induction of antibody‐mediated tumor cell killing 121, 122.…”
Section: Antibody‐dependent Tumor Killingmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, PMN from patients who have been treated with recombinant human G‐CSF also express FcγRI, the high affinity receptor for IgG 119. Consequently, these PMN are more effective in inducing ADCC than are PMN from healthy, untreated donors 120. The receptor for IgA (FcαRI) is also constitutively expressed by PMN and in these cells seems to be the most potent of the Fc receptors for the induction of antibody‐mediated tumor cell killing 121, 122.…”
Section: Antibody‐dependent Tumor Killingmentioning
confidence: 99%
“…Many of the reports listed in Tables I and II discuss the anticancer effect of PMN via ADCC,27, 41, 46, 50, 64, 83, 116, 120, 122–126, 128, 129, 131–177 and many provide direct evidence of this antibody‐mediated antitumoral role of PMN in vitro. The first reports were published in 1974 and 1975 by Gale and Zighelboim 131, 132.…”
Section: Antibody‐dependent Tumor Killingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from various research groups have shown that neutrophils from G-CSF treated patients are more efficient that those from healthy donors in mediating the lysis of various tumour cells sensitised with polyclonal rabbit antiserum (Repp et al, 1991) or murine monoclonal antibodies (Elsässer et al, 1996;Michon et al, 1998;Valerius et al, 1993;Würflein et al, 1998). Among these studies, the findings of Elsaässer and co-workers (Elsässer et al, 1996) and those of Würflein and co-workers (Würflein et al, 1998) are closely related to the present ones.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CD64 on neutrophils is upregulated as a physiological response to microbial wall components, complement split products, and several cytokines such as interferon-c (IFN-c), interleukin-8 (IL-8), IL-12, and granulocyte-colony stimulating factor (G-CSF). [1][2][3] Therefore, CD64 may be a marker that is specific for infection, and its efficacy in the diagnosis of both systemic and local infections has been reported. [4][5][6] For the diagnosis of musculoskeletal infections seen in orthopedics practice, conventional markers such as CRP or PCT may not be effective.…”
mentioning
confidence: 99%